The r/wallstreetbets 'war machine': Explicating dynamics of consumer resistance and capture. (June 2023) - Jones, Hunter; Hietanen, Joel
Following the recent #GameStop 'market disruption' where r/wallstreetbets 'rogue' traders were able to momentarily topple billion dollar hedge funds, we employ Deleuze and Guattari's 'war machine' concept in order to comment on the potential of consumer resistance when matched up against global financial markets. While most extant theory follows the Foucauldian tradition in asserting that consumer resistance is a reaction to power, we use Deleuze and Guattari's immanent theorisation of desire to make the case for thinking of resistance as primary. Far from a hagiography of affective affirmation, our immanent perspective draws attention to how state and corporate forms are readily able to co-opt consumer resistance. Ultimately, we make the case for reorienting consumer resistance research away from seeking out ruptures and breaks in stable structures of power to asking a more difficult question: how can resistance be organised to avoid capture?